Standardization of allergen products: 3. Validation of candidate European Pharmacopoeia standard methods for quantification of major birch allergen Bet v 1. Issue 10 (28th April 2016) - Kaul, S.; Zimmer, J.; Dehus, O.; Costanzo, A.; Daas, A.; Buchheit, K. H.; Asturias, J. A.; Barber, D.; Carnés, J.; Chapman, M.; Dayan‐Kenigsberg, J.; Döring, S.; et al.
Abstract: Background: The BSP090 project aims at establishing European Pharmacopoeia Reference Substances in combination with the corresponding ELISA methods for the quantification of major allergens in allergen products. Two sandwich ELISAs proved suitable for quantification of Bet v 1, the major birch pollen allergen, in preceding phases of BSP090. Methods: Two Bet v 1‐specific ELISA systems were compared with respect to accuracy and precision in a ring trial including 13 laboratories. Model samples containing recombinant rBet v 1.0101 as well as native birch pollen extracts were measured independently at least three times in each facility. The assessment was completed with a comparative quantification of Bet v 1 in 30 marketed birch allergen products in one laboratory, simulating the future use as reference method. Results: In the collaborative study, both candidate ELISAs confirmed their suitability to quantify recombinant and native Bet v 1. ELISA‐A showed higher precision and lower interlaboratory variability, yet ELISA‐B exhibited slightly higher accuracy. Subsequent parallel measurement of Bet v 1 in a panel of 'real‐life' birch allergen products indicated better repeatability of ELISA‐B. Both systems detected substantial differences in Bet v 1 content between allergen products, but the effect was more pronounced using ELISA‐B due to persistently higher values compared to ELISA‐A. Conclusions: In the collaborative study, no deciding differences were observed between the two candidate ELISAs. Further comparison under conditions simulating the intended use combined with the criterion of long‐term availability enabled the selection of one Bet v 1‐specific ELISA for proposal as European Pharmacopoeia standard method.